To be or not to be digital, that is the question: firm innovation and performance - Ferreira, J.; Fernandes, C.; Ferreira, F. (Journal of Business Research, 2019)
Digital transformation has recently become a way to attain competitive advantages and company differentiation. However, what the implications are of the digitalization of processes for the innovative capability and performance of companies is still unclear. This study seeks to contribute to a better understanding of digital transformation by analyzing the factors that lead companies to adopt new digital processes and their consequences in terms of innovation and performance. Using a sample of 938 companies and multivariate statistical analysis, this study shows that entrepreneurs' and managers' profiles and these leaders' adoption of new digital processes contribute to these companies' greater competitiveness.